CMOS design of reconfigurable data-panning algorithm based sorter for 8-input, 8-bit digital data using the 0.35um library - Tolentino, Anthony S. (Animo Repository, 2022)
The aim of this study is to design a CMOS based data-panning algorithm sorter using Tanner Tools and LTSPICE software. Existing data sorter algorithms have circuit implementations with larger circuit components making the data sorting process more power consuming and had difficulties in hardware design implementation. It also aims to design a reconfigurable circuit that allows user to select a number of data to be simulated inside the data-panning based sorter. The design was able to simulate 8 inputs and be sorted from lowest to highest simultaneously after 8 clock cycles. It has also a minimum hardware component compared to the other data sorter algorithms in terms of multiplexers, data registers, and magnitude comparators. It uses 2*N multiplexers, N*(b+1) data registers, and N/2 magnitude comparators for N represents the number of inputs, while b represents the number of bits of the inputs. A total area of 1.35 mm2 for the entire reconfigurable datapanning sorter circuit using Tanner Tools has been designed with a power consumption of 555 mW and a frequency of 20 μS.